2014
DOI: 10.1007/s13197-014-1541-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of flaxseed fortified rice – corn flour blend based extruded product by response surface methodology

Abstract: Flaxseed imparted the evidence of health benefits in human being. Response surface methodology (RSM) was employed to develop flaxseed fortified rice -corn flour blend based extruded product using twin screw extruder. The effect of roasted flaxseed flour (RFF) fortification (15-25 %), moisture content of feed (12-16 %, wb), extruder barrel temperature (120-140°C) and screw speed (300-330 RPM) on expansion ratio (ER), breaking strength (BS), bulk density (BD) and overall acceptability (OAA) score of extrudates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
6
16
0
Order By: Relevance
“…Secondary reason is the nutty flavor of flaxseed which increased at it higher DFM incorporation. Ganorkar and Jain (2014b) reported similar results for development of roasted flaxseed flour incorporated extruded product. Increase in the barrel temperature also increased OAA score (Fig.…”
Section: Overall Acceptability (Oaa)supporting
confidence: 58%
See 2 more Smart Citations
“…Secondary reason is the nutty flavor of flaxseed which increased at it higher DFM incorporation. Ganorkar and Jain (2014b) reported similar results for development of roasted flaxseed flour incorporated extruded product. Increase in the barrel temperature also increased OAA score (Fig.…”
Section: Overall Acceptability (Oaa)supporting
confidence: 58%
“…Breaking strength can be well correlated with textural attributes of the product. Breaking strength in kgf was then calculated as mean of ten random determinations (Ganorkar and Jain 2014b).…”
Section: Breaking Strength (Bs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the addition of dietary fiber most often leads to reduce expansion volumes and increases the density of the extruded cereals, inducing harder textures and less crispiness [3]. This result is consistent with the results reported by Ganorkar and Jain [12], who showed that an increase in added flaxseed causes an increase in the hardness of the extruded products. In other studies, such as that by Brennan et al [5], have reported an increased breaking force with increasing wheat bran content up to 15% in extruded breakfast cereals.…”
Section: Textural Measurement (Hardness and Crispness)supporting
confidence: 90%
“…The extruded cereals from the mixtures 6 and 3, with similar amaranth contents (27.6 and 34.7 g/100 g respectively), resulted in the lowest density values (4.6 and 4.7 kg L -1 , respectively; Table 4). These results are consistent with those shown by Ilo et al [9], who evaluated the effect of extrusion-cooking process on the properties of extruded rice flour and amaranth blends and observed that amaranth had an important influence on the product density, resulting in a minimum value at an amaranth content of 30 g/100 g. Another report showed that the extrusion of rice flour and corn fortified with linseed leads to increases in the bulk density values [12].…”
Section: Bulk Densitysupporting
confidence: 90%